Anteseden dan konsekuensi keberlanjutan laba di sektor transportasi dan logistik yang diakibatkan dampak Covid 19 tahun 2018-2022 - Carolyn Natasya Imani; Khomsiyah Khomsiyah (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
Transportation and logistics companies have been significantly impacted of the COVID-19 pandemic, leading the fluctuations in profitability between periods. Pandemic has signaled instability in profit levels during this period. The study involves 17 transportation and logistics sector listed on the Indonesia Stock Exchange, using purposive sampling techniques. Data analysis was conducted using path analysis with SmartPLS 3.0 software. This research is among the few to consider profit persistence as an intervening variable, particularly in the context of the pandemic in the transportation and logistics sector. Path analysis approach was used with more sophisticated statistical tests than previous studies.